The Effect of Learning Facilities on the Learning Achievement of Class V Students: Pengaruh Fasilitas Pembelajaran Terhadap Prestasi Belajar Peserta Didik Kelas V - Rasyidah Rasyidah Listiana Hidayat; Ida Rindaningsih (Academia Open, 2022)
The main purpose of this study was to determine whether or not these learning facilities had an effect on the achievement of class V students. This study used a quantitative method to determine the effect of learning facilities on student achievement in class V MI Nurul Huda Ngampelsari. This study uses primary data in the form of questionnaires, and secondary data in the form of observation and documentation. Researchers used a population of 83 people who were students of class V MI Nurul Huda Ngampelsari, and samples were obtained from classes Va and Vb, totaling 56 students. The data analysis technique used tabulation of the questionnaire results using a Likert scale which was then processed using the SPSS application. The results showed a significance value of 0.007 ttable 2,004. From these figures, it can be concluded that there is an influence of learning facilities on the learning achievement of students of Class V MI Nurul Huda Ngampelsari. The result of the coefficient of determination or R Square is at 0.099 which means that the influence of the learning facilities variable on the learning achievement variable is 9.9% and the remaining 90.1% is influenced by variables not examined. Highlights: The study examines the impact of learning facilities on the achievement of class V students using a quantitative method and primary and secondary data. Tabulation of questionnaire results using a Likert scale and data analysis with SPSS showed a significant influence of learning facilities on student achievement. The coefficient of determination indicates that learning facilities account for 9.9% of the variation in student learning achievement, while other variables contribute to the remaining 90.1%. Keywords: learning facilities, student achievement, quantitative method, Likert scale, data analysis.